Comparative Study of Cytokeratin Immunostaining of Parotid Gland Parenchyma in Normal, Diabetic, and Excretory Duct Ligation of Mongrel Dogs - Hassan, Sherif Sayed; Alqahtani, Mashael Saeed (European Journal of Dentistry, 2022)
Objectives The present study aimed to give a glimpse of the normal distribution of intermediate filaments within the parotid gland parenchyma of mongrel dogs and to reveal the pathological changes that may occur as a result of the effects of diabetes mellitus or atrophy of the gland caused by the ligation of the excretory duct to discover whether there is a similarity in these pathological behaviors.Materials and Methods Twelve healthy mongrel dogs were used in the experiment and were divided into three groups: group I (the control group), group II (dogs with alloxan-induced diabetes), and group III (dogs with the right-side duct-ligated parotid gland). The dogs were sacrificed 45 days after the parotid excretory duct were tied. The right parotid gland of all groups was dissected and prepared for histological and immunohistochemical expression of cytokeratin 17 assay.Results Histological findings confirmed that the parotid gland parenchyma of the diabetic group had glandular atrophy characterized by the loss of gland structure, degenerated acini, and dilatation of the duct system. Moreover, there is a predominance of the fibrous component with the presence of fat cells within the gland compartments. On the contrary, the excretory duct-ligated group undergoes severe glandular atrophy of the previous character with the presence of duct-like structure as well as extravasation and vasodilatation. Immunohistochemical expression of cytokeratin 17 in control parotid using an immunoperoxidase technique showed that cytokeratin expression varies from negative to mild in all ducts and some serous acinar cells. The gland parenchyma of the diabetic group showed mild to strong cytokeratin expression of duct cells more concentrated in the apical part with moderate to strong expression of diffuse type in some serous acini. The intensity of cytokeratin 17 in gland compartments of the excretory duct-ligated group revealed a variation in expression that ranged from negative to strong diffuse staining throughout the gland.Conclusion The severity and prevalence of cytokeratin 17 in our results are predictive of the pathological influence of both diabetes mellitus and duct ligation on the cytokeratin intracellular filaments of the salivary gland parenchyma in a different way that interferes with saliva production and/or secretion leading to xerostomia.
Keywords: parotid gland; duct ligation; diabetes; cytokeratin 17